The Cost-Effectiveness and Competency Untold - An Analysis of Medical Tourism in Kerala with reference to Allopathic Medicine - Sindhu Joseph
The key benefits of medical tourism in the ‘God’s Own Country’ are relatively competitive prices, quality, timely and personal care. The article unveils the cost difference between Kerala and other cities and compares with the main competitors like US and Thailand. Primary concerns are quality care, which includes expected quality of animate and inanimate resources and procedures, Personal care, which makes them ‘feel at home’ and the cost of treatment, However, the perception-reality analysis indicates that there is a slight difference in these two variables, which calls for conscious and coordinated efforts. There is an increase in supply of medical tourism products leading to greater competition and commercialization.